Self-powered, visible-light photodetector based on thermally reduced graphene oxide–ZnO (rGO–ZnO) hybrid nanostructure - Zhan, Zhaoyao (2013)
Here we report a new type of self-powered, visible-light photodetector fabricated from thermally reduced rGO–ZnO hybrid nanostructure. The photocurrent generation of the photodetectors under zero-bias enables hybrid rGO–ZnO devices to work like photovoltaic cells, which could power themselves without electrical power input. The thermal treatment at elevated temperature not only reduces graphene oxide (GO) into reduced graphene oxide (rGO), but also dopes the ZnO nanoparticles with carbon atoms, enabling their visible-light photoresponse capability. The pronounced and fast photocurrent generation was attributed to the efficient charge transfer between the rGO and carbon-doped ZnO nanoparticles, which were in intimate contact. The efficient charge transfer of the rGO–ZnO hybrid nanostructures also indicates that there could be applications in other light energy harvesting devices, including solar cells, sensors and visible-light photocatalysis.